TRAJECTORIES OF ECOLOGICAL CRISES - Lyuri D.I. (My University, 2004)
On the basis of the analyzed long-term dynamics of various resources consumption, the equilibrium trajectory of resource-using evolution was constructed. Revealed are the reasons, making this trajectory unacceptable by society and thus directing it to crisis evolution path. Trajectories of particular ecological crises with different finals are considered. As shown, catastrophic final of ecological crisis is not the only possibility and the crisis can lead to successful recovery of equilibrium between nature and society with society development acceleration.